What is important in preweaning mortality? - Rautiainen, Eero; Suomi, Kaija; Nyberg, Matti (fi, 1997)
Data of 60 litters was analysed with multivariable regression models to find out risk factors for low piglet production and mortality. Litter size alone explained 80% of the variation of the number of weaned piglets, when intrapartal hypoxia, trauma and hypoglycaemia had been accounted for. Large litter size caused a higher risk of mortality because of lower birth weight of piglets in large than in small litters and because of the greater variation of weights. High mortality rate did not decrease mean weight gain of survived piglets within a litter when controlled for litter size.
Keywords: Ko; porsaat; sika; kuolleisuus